Impact of a tailored self-management education programme for older adults with knee osteoarthritis in a multi-ethnic country - Kamsan, Siti Salwana; Singh, Devinder Kaur Ajit; Tan, Maw Pin; Kumar, Saravana (UKM Press, 2024)
Self-management education program (SMEP) is essential in the knee osteoarthritis (OA) management. While the benefits of tailored SMEP have been highlighted in the literature, evidence on the effects of tailored knee OA SMEP for multi- ethnic populations, such as in Malaysia, remains limited. Therefore, the aim of this study was to conduct an intervention study on a tailored SMEP among Malaysian older adults who aged 60 years and above with knee OA. Participants aged 60 years and over with a diagnosis of knee OA were recruited. The intervention comprised four weekly structured group SMEP which was developed specifically for the multicultural population in Malaysia. Symptom’s severity and functional performance were assessed at baseline and six-week follow-up using the Knee Injury and Osteoarthritis Outcome Score questionnaire (KOOS), 30 seconds sit to stand (30sST), time up and go (TUG), chair sit and reach (CSR), back stretch (BS), handgrip strength (HGS) and two-minute walk (2MW) tests. Of the 32 individuals recruited, 30 participants, mean age of 66.77 (±6.42) years, completed the post-intervention assessment. Improvements in mean KOOS domains scores were observed by between 1.3% - 8.6% from baseline to follow-up. Significant differences between baseline and follow- up scores were identified for 30sST (p < 0.05), TUG ( p < 0.001) and 2MW (p < 0.001) tests. A 4-week tailored SMEP delivered face to face by a physiotherapist, improved lower limb muscle strength, mobility, balance and endurance. Larger randomized controlled trials regarding the long-term effects of SMEP for older adults with OA is warranted.